1996
DOI: 10.1021/ja960874e
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Tunneling Microscopy of Metal Phthalocyanines:  d7 and d9 Cases

Abstract: Scanning tunneling microscopy (STM) images of cobalt(II) phthalocyanine (CoPc), copper(II) phthalocyanine (CuPc), and mixtures of the two adsorbed on the Au(111) face are reported. Based upon the stability and ease of obtaining molecular images, CoPc appears to adsorb more strongly than CuPc on Au(111), but both species provide images showing submolecular structure. The mixed CoPc and CuPc films also provide high-quality images showing details of the internal structure of the metal phthalocyanine. A particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

48
400
1
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 376 publications
(451 citation statements)
references
References 38 publications
48
400
1
2
Order By: Relevance
“…It was reported that H 2 Pc molecules form a quasi-square lattice on highly oriented pyrolytic graphite surface [25], and similar ordering was observed for FePc [11,12], CoPc [2,[13][14][15], NiPc [11], CuPc [2,15,16] and SnPc [17].…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…It was reported that H 2 Pc molecules form a quasi-square lattice on highly oriented pyrolytic graphite surface [25], and similar ordering was observed for FePc [11,12], CoPc [2,[13][14][15], NiPc [11], CuPc [2,15,16] and SnPc [17].…”
Section: Resultssupporting
confidence: 58%
“…The ridge of the herringbone structure is perpendicular to one of these quasi-close-packed directions. For an MPc film, quasi-square lattices were commonly formed when the coverage was close to a monolayer, as clearly demonstrated for the molecules of CoPc [2,[13][14][15] and FePc [11,12].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Both polyaniline [12,[18][19][20][21] and copper phthalocyanine (CuPc) thin films [8,13,[22][23][24][25][26][27] (schematically illustrated in Figure 5) can be produced by vapor deposition compatible with ultrahigh vacuum photoemission. These films can be grown very thin (100 Å or less) and are free of solvent contamination.…”
Section: Some Background On the Organic Semiconductors Comparedmentioning
confidence: 99%
“…Indeed, with adsorption on metallic substrates copper phthalocyanine exhibits an electric dipole as the molecular center copper atom is not in the same plane as the surrounding ligand, and adopts a position that is typically closer to the interface [27]. The changes in the copper phthalocyanine orientation and dipole make this metalorganic semiconductor a useful adsorbate for the study of effects of dipole interactions at a heterojunction interface [13].…”
Section: Some Background On the Organic Semiconductors Comparedmentioning
confidence: 99%